Evolving approaches to understanding natural hazards - Tobin, Graham A.; Montz, Burrell E., 1951- (Cambridge Scholars Publishing, 2015)
The 21st century presents many challenges to the hazard manager; dynamic climatic conditions combined with population growth, rapid urbanization, and changing socio-economic relationships are reshaping disaster impacts, community responses, and social safety mechanisms. Indeed, human vulnerability is constantly restructured by the ongoing interplay of physical, social, economic, and political forces. At the same time, reducing vulnerability and enhancing community resilience require policies aimed at mitigating the consequences of disasters as they affect different locations and different grou.